Impact of Seismic Waves on Structures in a Deformable Medium (Texas Journal of Engineering and Technology, 2022)
In this paper, we study the stress-strain state that occurs when a cylindrical body of arbitrary density is exposed to and around it. The problem is solved with the help of special functions and the Gauss method, numerical results are obtained.